Understanding consumer purchase intention to purchase sustainable fashion: the moderating role of gender perception - Melvina Adeline Tjokrosoeharto; Eristia Lidia Paramita (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
The growing trend of sustainable fashion products has put the company to deal with the challenge of gender perception in quality, design, and price since fashion is consumers’ self-presentation of personality and taste. This study aims to examine the influence of sustainable fashion products to consumer purchase intention with gender perception as the moderating role. Results of moderated regression analysis (MRA) on 267 samples suggests that sustainable fashion product has a positive influence toward consumer purchase intention and the gender perception significantly moderates the Indonesian consumer purchase intention. Additionally, this study gained information that respondents were well aware with the effort of sustainability in fashion, and it believed can protect the environment.